Heavy metals distribution characteristics of FGD gypsum samples from Shanxi province 12 coal-fired power plants and its potential environmental impacts. (1st December 2017) - Hao, Ying; Li, Qiu; Pan, Yun; Liu, Zixing; Wu, Simiao; Xu, Yuebu; Qian, Guangren
Highlights: Heavy metals pollutant characters in FGD gypsums in China were evaluated. Leaching toxicity results exceeded environment quality standards for surface water. Chemical species of heavy metals displayed different characters. All the heavy metals in FGD gypsum posed risks to the environment. Annually leachable amount of heavy metals from FGD gypsum was estimated. Abstract: Flue gas desulphurization (FGD) gypsum samples were collected from 12 power plants in Shanxi province in China. The total concentrations of Zn, Mn, Pb, Cr, Cd and Ni in FGD gypsum were determined. The chemical speciation and leaching toxicity were also analyzed. The total concentration ranges of Zn, Cr and Mn were at 40.1–96.1 mg/kg, 12.9–61.1 mg/kg and 2.1–56.1 mg/kg respectively. While the concentrations of Ni, Pb and Cd were relatively lower, with total concentration fell into the ranges of 0.7–31.7 mg/kg, 0.01–13.3 mg/kg and ND-1.6 mg/kg respectively. The average values appeared to follow the order of Zn > Cr > Mn > Ni > Pb > Cd. Synthetic Precipitation Leaching Procedure (SPLP) test results were all below the China's regulation level of leaching toxicity for heavy metals, while exceeded environmental quality standards for different classes of surface water in China. Selective sequential extraction (SSE) used for chemical speciation analysis showed that different heavy metals distributed variously in each extraction fraction. The bioavailability of major heavy metals for FGD decreased in the order of Mn > Zn > Cd > Cr > Pb > Ni, while their mobility decreased in the order of Cd > Mn > Ni > Pb > Zn > Cr. Risk assessment code (RAC) analysis suggested that heavy metals in all samples from Shanxi province posed risks to the environment. Especially, elements of Zn and Mn posed a very high risk. Estimation of annually leaching amount of heavy metals from FGD gypsum was calculated.